The expectations and of the population as a basis for the development of the communication program of conscientious attitude formation of the contact audience to the preventive treatment of oncology diseases: on the example of Tomsk; Ponte; Vol. 72, iss. 11 - Nadezhdina E. Yu. Elena Yurjevna; Evstegneeva E. A. Evgeniya Aleksandrovna; Kurikova N. V. Nataljya Vladimirovna; Plastun E. V. Evgeniya Vladimirovna; Shtogrina Yu. I. Yuliya Ivanovna; Ruchina A. V. Aleksandra Viktorovna (2016, 2016)
Title screen